(untitled) - Richard Heatley (Cambridge, Massachusetts, 1995)
The book provides a concise up-to-date review of H. pylori infection, current approaches ti its diagnosis and treatment, and the position of H. pylori eradication in the management of gastrointestinal disorders
Keywords: gastritis - hanbooks,helicobacter pylori infections - hanbooks, manuals, etc,peptic ulcer - handbooks